Analysis of the role of antibody-dependent cellular cytotoxic antibody activity in murine neonatal herpes simplex virus infection with antibodies to synthetic peptides of glycoprotein D and monoclonal antibodies to glycoprotein B. - Kohl, S (1990)
The role of antibody in neonatal herpes simplex virus (HSV) infection remains controversial. A battery of well-characterized monoclonal antibodies to HSV glycoprotein B (gB), and polyclonal antibodies against synthetic peptides of predicted epitopes of HSV glycoprotein D (gD) were used to determine in vitro functional activity and association with protection against lethal infection in a murine model of neonatal HSV disease. Antiviral neutralization activity of HSV was not associated with antibody-dependent cellular cytotoxicity (ADCC) activity to HSV-infected cells in vitro. In a model of high dose challenge (10(4) PFU), protection was not afforded by any antibody alone, but was by antibody plus human mononuclear cells, and highly associated with ADCC functional activity (P less than 0.001). In a low dose challenge model, neutralizing activity of antibody alone was associated with protection in vivo (P less than 0.001). Of the nine neutralizing epitopes of gD in vitro, eight were predicted surface regions. Four of the five epitopic sites of gD (2-21, 267-276, 288-297, and 303-312) that were determined to be important targets of ADCC and in vivo protection were also predicted to be surface regions. The only exception was the antiserum to region 52-61 which was predicted to be buried and also showed these activities. ADCC as well as neutralizing antibody activity are important in protection against neonatal HSV infection.